2020
DOI: 10.1080/15384101.2020.1743911
|View full text |Cite
|
Sign up to set email alerts
|

Metformin activates AMPK/SIRT1/NF-κB pathway and induces mitochondrial dysfunction to drive caspase3/GSDME-mediated cancer cell pyroptosis

Abstract: Metformin activates AMPK/SIRT1/NF-κB pathway and induces mitochondrial dysfunction to drive caspase3/GSDME-mediated cancer cell pyroptosis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 73 publications
(98 reference statements)
2
87
0
Order By: Relevance
“…Thus, pyroptosis is an immune-stimulatory form of cell death and can synergize with immune checkpoint agents to improve the efficacy of immune therapy. Recently, metformin has been reported to induce pyroptosis in cancer cells [134,135]. Given that metformin promotes antitumor immunity and improves efficacy of ICIs in malignant cancers [136][137][138][139], it is possibly that induction of pyroptosis of cancer cells by metformin may reprogram TIME toward "infiltrated-inflamed".…”
Section: Induction Of Pyroptotic Cell Death By Immune Therapymentioning
confidence: 99%
“…Thus, pyroptosis is an immune-stimulatory form of cell death and can synergize with immune checkpoint agents to improve the efficacy of immune therapy. Recently, metformin has been reported to induce pyroptosis in cancer cells [134,135]. Given that metformin promotes antitumor immunity and improves efficacy of ICIs in malignant cancers [136][137][138][139], it is possibly that induction of pyroptosis of cancer cells by metformin may reprogram TIME toward "infiltrated-inflamed".…”
Section: Induction Of Pyroptotic Cell Death By Immune Therapymentioning
confidence: 99%
“…Many previous studies have focused on cellular oxidative stress as a primary mechanism for positive effects of metformin on colon cancer. [ 17,32,46 ] However, disturbances in the SIRT3 activity and expression might result in mitochondrial dysfunction and cell death. [ 47 ] However, there is no study regarding the underlying metformin mechanism against the CRC cells and its effects on enzyme Sirt3.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Previous studies have shown that metformin can exert antineoplastic effects by recruiting the kinase enzyme activated by adenosine monophosphate (AMPK) and reducing the phosphorylation of protein kinase B, mammalian target of rapamycin (mTOR), and p70S6k in different types of tumors. [ 18,19 ] In addition, metformin regulates apoptosis signaling [ 20 ] by inhibiting phosphorylation of BAD and Bcl‐2, procaspase 9, procaspase 3, and procaspase 7, and upregulation of BAD, cytochrome c, and Apaf‐1 protein. [ 21,22 ] However, metformin is capable of affecting the mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%
“…GSDME-NT can be stimulated by caspase-3, which is similar to the GSDMD-NT, leading to the formation of pores in the cellular membrane region ( Fig. 1 ) [50] , [51] . The actual role of GSDME in stimulating pyroptosis upon apoptosis has largely been constrained in the extensive investigations [51] .…”
Section: Introductionmentioning
confidence: 97%
“…1 ) [50] , [51] . The actual role of GSDME in stimulating pyroptosis upon apoptosis has largely been constrained in the extensive investigations [51] . During the mitochondrial apoptotic process, GSDME plays a redundant role in channel formation.…”
Section: Introductionmentioning
confidence: 99%